2023
DOI: 10.3390/coatings13071229
|View full text |Cite
|
Sign up to set email alerts
|

Properties and Performance of TiAlSiN and AlCrN Monolayer and Multilayer Coatings for Turning Ti-6Al-4V

Abstract: The high chemical activity, low thermal conductivity, and high strength of titanium alloys lead to severe tool wear during cutting. The coating applied to the tool surface insulates the effect of heat and chemical reactions. TiAlSiN coating and AlCrN coating are two representative coatings with excellent properties in TiN-based and CrN-based applications, respectively. Three types of nanocoatings—TiAlSiN monolayer, AlCrN monolayer, and TiAlSiN/AlCrN multilayer—were prepared, and the microstructure, mechanical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Finite element modeling has been employed to verify the effect of the design of magnetron-sputtered multilayer Ti/AlN coatings on the distribution of residual stress [17]. However, it was also found that the multilayer AlCr/AlTi-based coating cannot prevent diffusion leading to a reduced tool life; instead, it may cause worse diffusion wear due to the interlayer defects compared to a AlCrN monolayer coating with a better adhesion strength to the substrate [18].…”
Section: Introductionmentioning
confidence: 99%
“…Finite element modeling has been employed to verify the effect of the design of magnetron-sputtered multilayer Ti/AlN coatings on the distribution of residual stress [17]. However, it was also found that the multilayer AlCr/AlTi-based coating cannot prevent diffusion leading to a reduced tool life; instead, it may cause worse diffusion wear due to the interlayer defects compared to a AlCrN monolayer coating with a better adhesion strength to the substrate [18].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the surface texture, surface coating can improve the surface friction properties. AlCrN coatings have been widely used in cutting tools owing to their excellent material properties, including high hardness, wear resistance, and chemical stability [14][15][16]. Mo et al [17] investigated the sliding friction properties of an AlCrN coating and discovered that it exhibited excellent wear resistance, with the primary friction mechanism being a combination of wear and oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…Das et al [27] developed a nanocomposite AlTiSiN coating deposited using scalable pulsed-power plasma, which improved the surface finish of AISI D6 steel samples during turning. Liu et al [28] investigated the microstructure and oxidation resistance of three nanocoatings (TiAlSiN/AlCrN multilayer, AlCrN monolayer and TiAlSiN monolayer). It was found that the AlCrN coating has the highest adhesion strength, while the TiAlSiN coating has the lowest adhesion strength among the coatings tested.…”
Section: Introductionmentioning
confidence: 99%